STUDI PERILAKU TERHADAP KONSUMEN MUSLIM DI SEMARANG : RELIGIOUS MOTIVE DAN ECONOMIC MOTIVE DALAM PROSES PENGAMBILAN KEPUTUSAN PEMBELIAN KONSUMEN - Bahren, Zul (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
ABSTRAK This study aims to determine the effect of Religious and economic motive of Customer Decision making process on Wardah halal cosmetic products in Semarang. The sample used in this study is the students in Semarang who used Wardah halal cosmetic products. This research method used questionnaire as research instrument. Non-probability sampling technique is used as a sampling technique. This research data has been collected 100 questionnaires from students in Semarang who used Wardah halal cosmetic products in Semarang. SEM PLS analysys software is used to determine the effect of the variables involved. These results indicate that the Religious motive and Economic motive has significant relationship with Customer Decision making process on Wardah halal cosmetic products in Semarang. Keywords: Religious motive; economic motive; Customer Decision making process.